The art of analogy in the poetry of Aws bin Hajarh - Al-Wahaibi, Said Obaid Abdullah (Journal of Arabic Language Sciences and Literature, 2025)
Simile represents one of the most prominent artistic devices in classical Arabic poetry, playing a vital role in illustrating meanings and shaping vivid imagery in a stylistically impactful manner. This study focuses on the poetry of Aws ibn Ḥajar, a renowned pre-Islamic (Jāhilī) poet known for his eloquent use of similes that reflect the spirit of his environment and era. Despite his literary significance, detailed studies on simile in his poetry remain limited. The primary aim of this research is to explore the use of simile in Aws ibn Ḥajar’s poetry by identifying the types of similes he employed, their diversity, and their function in constructing poetic imagery. It further examines the aesthetic and rhetorical features of simile in his work and how his cultural and environmental context influenced these expressions. The study adopts a descriptive-analytical approach, supported by inductive analysis of selected poetic texts that include similes. Through close reading and literary examination, the research uncovers the artistic dimensions of simile in Aws ibn Ḥajar’s poetry. The findings reveal that simile constitutes a fundamental element in his poetic structure. His use of both direct and complex similes demonstrates high rhetorical proficiency and contributes significantly to the richness and expressiveness of his verse. The study recommends further scholarly attention to simile and figurative imagery in the poetry of other Jāhilī poets to better understand the artistic depth of early Arabic literature.